Improving the Ranking of Russian Smart Cities - Lyaskovskaya , Elena A.; Khudyakova , Tatyana A.; Shmidt , Andrey V. (Economy of Regions, 2022)
Digitalisation and urbanisation have led to smart city becoming a key element of the concept of sustainable development, acting as an object of sustainable development management. Thus, a smart city must become a sustainable smart city. The first step is the creation of the system of current state diagnostics or smart city ranking. This ranking should consider international standards, the specificity of Russian urban development, as well as various components of sustainable development. It is hypothesised that the ranking methodology reflecting these components can be used to analyse the dynamics of sustainable development based on the chosen criteria and factors. To assess social, environmental, economic and management components of cities with a population of more than 100,000 people, the proposed technique relies on the theory of multiple comparisons and the distance method. The comprehensive assessment of smart cities includes 71 indicators grouped into 8 criteria: people, social cohesion, economy, management, ecology and the environment, transport, urban planning, technology. The study analysed Russian and international statistical databases, as well as data from industry agencies. The ranking of 171 cities was developed; regional features of Russian smart cities were identified using the selected criteria. The cities of Moscow, St. Petersburg, Balashikha, Krasnodar and Kazan are at the top of the ranking. The leadership of the Central Federal District and a significant differentiation by the criteria “urban planning” and “technology” are the key regional features. Annual comprehensive assessment can be used to track the dynamics of the development of smart cities, evaluate the effectiveness of decision-making and implementation, plan urban development based on federal and regional digitalisation projects, as well as create strategies to enhance the sustainability of Russian smart cities.